The Influence of Corporate Governance and Profitability on Corporate Value with Corporate Social Responsibility as a Mediating Variable - Suci Anggraini; Atmaji Atmaji (Eduvest - Journal of Universal Studies, 2025)
The purposes of this study is to examine the effect of corporate governance and profitability on firm value, and to test whether corporate social responsibility mediates the effect of corporate governance and profitability on firm value. This research was conducted in the energy and basic material sectors from 2013-2022. The number of samples in this study were 610 data, which were obtained through annual reports listed on the Indonesia Stock Exchange. The results of the analysis show that board size, board independence, profitability, corporate social responsibility have a positive influence on firm value. In addition, corporate social responsibility mediates the positive influence of board size, board independence and profitability on firm value..